Uso da inseminação artificial em tempo fixo e do cruzamento industrial para intensificar a atividade pecuária na sub-região do Médio Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The objective of this study was to evaluate the use of Fixed Time Artificial Insemination (FTAI) and crossbreeding in the sub-region of the Middle Amazon to promote technological intensification and develop animal production activity. Two experiments were conducted on a private farm that works with beef cattle under rotational grazing. Initially, sixty-eight cyclic heifers were subjected to FTAI with three bulls, one of the Aberdeen Angus and two Nelore. With one Nelore proved for superior fertility. The heifers were stratified in three groups according to the bull used: Group 1 - Aberdeen Angus (n=35); Group 2 - Nelore (n=18); and Group 3 - Nelore proved for superior fertility (n=15). The empty heifers were resynchronized with the same hormonal treatment and inseminated with semen from the bulls of Groups 1 and 3, renamed as Group 1R (n=19) and Group 3R (n=18). Both in synchronization and resynchronization, pregnancy diagnosis was performed 45 days after insemination. With the birth of the calves, a second experiment was carried out, selecting 24 primiparous cows and their respective progenies. The experiment was balanced for the paternal breed and sex of the calves and designed into two groups: Group N - Nelore calves (n=12) and Group M - Crossbred calves (n=12). The primiparous cows were evaluated for body condition score (BCS) and the calves for live weight, at birth/parturition, and after 60 and 150 days. The variables were subjected to statistical tests of Chi-square (conception rate), Kruskal-Wallis (BCS), Analysis of Variance, and Tukey test (calf weight), all at the significance level of 5%. Furthermore, a financial simulation was performed comparing natural breeding and purebred calf production. In the first experiment, no statistical difference was observed for conception rate in synchronization and resynchronization, respectively, 45.6% and 48.6% (p>0.05). In resynchronization, Group 3R heifers also showed a better result (61.1% vs 36.8%), but not statistically significant (p>0.05). In the second experiment, primiparous cows showed good body conditions with a loss of score throughout the study, at parturition they had a BCS of 3.8 and 4.0, reaching 3.3 and 3.2 at 150 days, respectively, in groups N and M (p>0.05). Crossbred calves were born on average 8 kg lighter (30.7 vs 38.7 kg), but showed higher daily weight gain and consequently higher live weight at 60 and 150 days of life, respectively, 83.8 vs 72.6 and 156.7 vs 136.6 kg (p<0.05). In financial simulation was observed that the cost-return ratio was favorable for the application of FTAI when compared to natural breeding, resulting in a higher refund with the use of this biotechnology. Crossbred calves, on the other hand, provided lower revenue when compared to purebred calves, motivated by the inferiority in the conception rate of this group. But in general the FTAI applied proved to be feasible to promote the intensification of beef cattle in the Middle Amazon with positive effects on productivity, which can contribute to minimize the impacts of cattle ranching activity on the Amazon environment.
Keywords: Pecuária - Amazonas; Gado - Reprodução; Bovinos - Inseminação artificial; OUTROS: CIENCIAS AMBIENTAIS; Sustentabilidade; Índices zootécnicos; Produtividade; Retorno econômico